1996
DOI: 10.1046/j.1365-2036.1996.43185000.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow‐up after cure of Helicobacter pylori infection with 4 days of quadruple therapy

Abstract: Four days of quadruple therapy seems to be an effective therapy for the eradication of H. pylori as evidenced after long-term follow-up. Our biopsy methodology is reliable in identifying treatment failures 5-6 weeks post-treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Reinfection during the follow up period is extremely unlikely 32. Although only a single genotype was detected before treatment, other genotypes may already have been present before treatment at a low concentration or may have remained undetected owing to sampling variation during endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Reinfection during the follow up period is extremely unlikely 32. Although only a single genotype was detected before treatment, other genotypes may already have been present before treatment at a low concentration or may have remained undetected owing to sampling variation during endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…One further step would be taken towards the ultimate goals of identifying a one‐dose ‘magic bullet’ which eliminates H. pylori and prevents the emergence of multiple drug resistant strains of the bacterium. There are preliminary studies of H. pylori eradication regimens of 1–6 day duration but these are pilot experiments, performed in small numbers of patients with sub‐optimal design 5 –8 . The aim of this study was to test two 3‐day H. pylori eradication regimens against a standard one‐week regimen, in a prospective, randomized format with a minimum of 50 patients in each study arm 9…”
Section: Introductionmentioning
confidence: 99%
“…The results corroborate those of previous reports that quadruple therapies present a promising alternative to current standard first‐line Helicobacter pylori therapies 15 , . 23 –30 Those studies have shown that 4 days of quadruple therapy achieve cure rates over 90% and that a 14‐day quadruple therapy will cure even patients with in vitro metronidazole resistance 15 …”
Section: Discussionmentioning
confidence: 99%